The reality of smart city development management in the comprehensive development plan for the city of Baghdad 2030 - الشيخلي عبد الرزاق ابراهيم; علوان نوال عبد الكريم (Journal of Economics and Administrative Sciences, 2018)
Abstract Abstract has many advantages as has historically been one of the regions leading cultural centers . for centuries , it has been a center of commertial and financial operations in Iraq. it is also rich in archeological sites and natural resources, but because of its wars and implementation of urban development strategies are effective and sustainable , so contracted the secretariat of Baghdad with the company (khatib and scirntiffic) for the preparation of the comprehensive development plan for the city of Baghdad in 2030 and funded by the world bank and the fact that the plan was approved ( three stages of it ) and only one phase remains the fourth stage, which is under discussion the aim of the research is to identify the extent to which it is oriented towards the smart cities approach that the cities of the world are dealing with today through a sample representing the consultative team of the comprehensive plan of the city of Baghdad 2030 and its supporters in the municipality of Baghdad which number (51) people tha data was collected by means of several tools, namely, questionnaire and personal inter views and a number of statistical methods were used to process the information including the comparative rations of the empirical analysis to test the hypotheses of the study, which states that there is a significant correlation between the study variables, there was a significant correlation between the study variable varibles, the effects of significant significance among the variables of all study and the study reached a set of conclusions, the most important of which is the comprehensive development plan for the city of Baghdad requires the integration of all its vocabulary with in the development of smart cities